Air Plasma Mitigation of Shock Wave - Kuo, Spencer P. (European Journal of Applied Sciences, 2021)
Theory is presented to show that shock wave structure can be modified via interacting with an air plasma plume generated symmetrically in front of a shock wave generator. Electron jet in the plasma plume deflects the impinging airflow via momentum transfer collisions. Symmetrical deflection makes it easy to satisfy the conservation of transverse momentum between the airflow and plasma. The charge transfer between N2+ and N2 randomizes the impinging airflow to increase the deflection angle. The flow deflection increases the effective cone angle of the shock generator; as the effective cone angle exceeds a critical value, the shock becomes detached and faded. Experiments were conducted in a Mach 2.5 wind tunnel to mitigate shock wave via air plasma deflection. A non-thermal air plasma was symmetrically generated, in front of a wind tunnel model by on-board 60 Hz periodic electric arc discharge, as a deflector for shock wave mitigation. The results show a transformation of the shock from a well-defined attached shock into a highly curved shock structure, which has increased shock angle and appears in diffused form. Shown in a sequence with increasing discharge intensity, the transformed curve shock in front of the model moves upstream to become detached with increasing standoff distance from the model and is eliminated when the discharge is near the peak. The steady of the incoming flow during the discharge cycle is manifested by the repetition of the baseline shock front. The experimental observations confirm the theory and efficacy of this air plasma mitigator.